المتخيل السردي ودوره في الكشف عن جماليات الصحراء المرجعي - صماري, بوعلام; عليوات, سامية (University of Eloued جامعة الوادي, 2024)
إن للكتابة السّردية دور في جذب السيّاح والتّعريف بالصّحراء؛ من عادات وتقاليد وفضاءات مكانية، وثقافة وعمران وأغاني شعبية وتفكير جمعي ... لاستقطاب القارئ وجذبه قصد اكتشاف ما تموج به الصحراء من عوالم حضارية، ومعرفية وسياحية. حيث أسهمت روايات الصديق حاج أحمد الزيوانيى -مملكة الزّيوان- في التّعريف بعادات وتقاليد الصّحراء، وما يميز البيئة الصحراوية؛ كالقصور بهندستها المتفرّدة ومواد البناء القديمة بما يضفي على المكان عراقة وأصالة تغوي القارئ بزيارتها لاستكشاف عبق التاريخ والفن. Narrative writing has a role in attracting tourists and introducing the desert. From customs, traditions, spatial spaces, culture, urbanism, folk songs and collective thinking... to attract the reader and attract him in order to discover the civilizational, knowledge and tourism worlds that ripple through the desert. Where the novels of Al-Siddiq Haj Ahmed Al-Zaywani - the Kingdom of Al-Zaywani - contributed to defining the customs and traditions of the desert, and what distinguishes the desert environment. Such as palaces with their unique architecture and ancient building materials, which give the place nobility and originality, seducing the reader to visit it to explore the fragrant history and art.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج07 . ع.01. جامعة الوادي
Keywords: المتخيل السردي; البيئة الصحراوية; مملكة الزيوان; مصاحبات الخطاب